A concepção do processo de reescrita do aluno a partir de práticas de sala de aula em uma turma do 3° ano do ciclo de alfabetização - Santos, Cícero Gabriel dos (2018)
This thesis, of a qualitative-interpretative nature, developed within a school of the municipal network of Esperança - PB, has as corpus of analysis texts generated in the contact with the teacher and with the students of a class of the 3rd year of the Literacy Cycle, through a semistructured interview; texts generated in the transcription of the classes filmed and texts produced by the students, under the guidance of the collaborator, in the second semester of the 2016 school year. It is based on a discursive perspective of language and supported by the theoretical and methodological contributions of the New Studies of Literature (KLEIMAN, 1995; ROAR, 2009; SOARES, 2016a, STREET, 2014), in the presuppositions of Bakhtin's thought, and responsiveness (BAKHTIN, 2011; BAKHTIN / VOLOSCHINOV, 2009; SOBRAL, 2009) and in the studies that have directed the teaching of the written language modality (ANTUNES, 2003; BENTES, 2012; BUNZEN, 2006, MENEGASSI, 2010; REINALDO 2003 ; VAL; VIEIRA, 2005; GERALDI, 2013; SERCUNDES 2011), the present thesis aims to understand the conception of the process of rewriting of the student from the classroom practices in a class of the 3rd year of the Literacy Cycle. Based on the articulation of the information gathered in the research, we established 3 (three) thematic axes for discussion and data analysis: 1) representations about the practice of teaching writing; 2) representations about the mediating actions undertaken for the development of the rewriting process; and, finally, 3) representations about the student's rewriting conception. From the systematization of the teaching of writing proposed by the teacher, we return to the assertion that human activities are directly related to the use of language, which is performed through oral and written utterances, uttered by members of the most varied fields of human knowledge. activity (BAKHTIN, 2011). Therefore, given the different situations and needs of interaction, the statements are consolidated and are reference for the production of new texts. Thus, only one application of an interactionist view of writing could be an analysis of classroom practices and a project of understanding student rewriting. Under this aspect, the results of this thesis indicate that the representations of the work with the writing reveal the adoption of a procedural and interactive perspective, since the systematization of the teaching of this modality dialogues with the vision that it is necessary to create significant practices of learning of the writing; that the oral interventions directed collectively towards the group in the revision process lead the learner to become an active participant, having to collaborate with the establishment of the dialogue during the activity, although the prioritization of aspects related to textualization should configure rewriting as a correction activity; that the identification of the changes made by the children and the analysis of their interpretations about these actions favor the observation of a conception of rewriting still under construction, a finding that was only possible thanks to the discourse established between researcher and students, a necessary action for the consolidation of the rewriting process in the early years.